The Role of Calcium–Calcineurin–NFAT Signaling Pathway in Health and Autoimmune Diseases - Park, Yune-Jung; Yoo, Seung-Ah; Kim, Mingyo; Kim, Wan-Uk (Frontiers in Immunology, 2020)
Calcium is an essential signaling molecule that controls a wide range of biologic functions. In the immune system, calcium signals play a pivotal role in diverse cellular functions, including cell proliferation, differentiation, apoptosis, and a number of gene transcriptions. During an immune response, the engagement of T-cell and B-cell antigen receptors induces depletion of the intracellular Ca2+ store, and then activates store-operated Ca2+ entry (SOCE) to raise the intracellular Ca2+ concentration, which is mediated by the Ca2+ release-activated Ca2+ (CRAC) channels. Recently, identification of the stromal interaction molecule (STIM) and Orai1, two essential regulators of the CRAC channel, has broadened our understanding of the regulatory mechanisms of Ca2+ signaling in lymphocytes. Repetitive or prolonged increase in intracellular Ca2+ is required for the calcineurin-mediated dephosphorylation of nuclear factor of activated T‐cell (NFAT). Recent data indicate that Ca2+-calcineurin-NFAT1 to 4 pathways are dysregulated in autoimmune diseases. Therefore, cyclosporine and tacrolimus, calcineurin inhibitors, have been used for the treatment of autoimmune diseases, including rheumatoid arthritis and systemic lupus erythematosus. Here, we review the role of the Ca2+-calcineurin-NFAT signaling pathway in health and diseases, focusing on the STIM and Orai1, and discuss the deregulated calcium-mediated calcineurin-NFAT pathway in autoimmune diseases.